Biosynthesis of nickel oxide nanoparticles using Ficus Auriculata leaf extract and its photocatalytic activity in methyl blue dye degradation - Nurhazirah Abdullah, 1995-, author; Mustaffa Shamsuddin, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2018